Tactile temporal discrimination in patients with blepharospasm. Issue 7 (6th November 2007) - Fiorio, M; Tinazzi, M; Scontrini, A; Stanzani, C; Gambarin, M; Fiaschi, A; Moretto, G; Fabbrini, G; Berardelli, A
Abstract : Background: Blepharospasm is an adult-onset focal dystonia that causes involuntary blinking and eyelid spasms. Studies have shown the presence of sensory deficits associated with dystonia. Aim: To rule out any confounding effect of muscle spasms on sensory performance in affected and unaffected body regions of patients with blepharospasm and with hemifacial spasm. Methods: Participants (19 patients with blepharospasm, 19 patients with hemifacial spasm and 19 control subjects) were asked to discriminate between two stimuli that were either simultaneous or sequential (temporal discrimination threshold, TDT). Pairs of tactile stimuli were delivered with increasing or decreasing inter-stimulus intervals from 0 to 400 ms (in 10-ms steps) to the hands or on the skin over the orbicularis oculi muscle. Results: Tactile stimuli elicited similar TDTs in control subjects and patients with hemifacial spasm, but significantly higher TDTs in patients with blepharospasm, regardless of whether stimuli were applied to the orbicularis muscle or the hand. Conclusions: As TDT was abnormal in unaffected body regions of patients with blepharospasm, and patients with hemifacial spasm processed tactile stimuli normally, TDT deficits in blepharospasm depend on central rather than peripheral factors. This study further supports the link between focal dystonia and impaired temporal processing of somatosensory inputs.